Web3 and blockchain applications for real world problems - Soh, Nathan (Nanyang Technological University, 2024)
The rise of Social media has disrupted the professional networking space with the popular platform LinkedIn, with a total of over 1 billion users on the platform. It gives people a platform to post meaningful content, connect and make conversations with like-minded individuals and industry leaders. It also gives users a streamlined process to apply for jobs, research on companies and to add credentials such as their professional experiences and certifications to establish their professional image. However, in most social media platforms such as LinkedIn, privacy of user data is almost non-existent as the companies behind the platforms own all this data on their servers and sells the data to data brokers to give users more advertised advertisements. In fact, selling data accounts for a large proportion of these companies’ revenues. Other than that, LinkedIn also contains many fake job listings with scammers on the other end, and users who inflate their profile by putting fake credentials. The creation of a blockchain-based professional networking platform could solve these issues using the transparent, immutable and verifiable nature of the blockchain. In this paper, I propose a rudimentary implementation of such an application, which will contain classic features of social medias such as posting content and images, but also provide a way to handle credential verification, rewards for meaningful content, and fees to mitigate the fake job listings.